On the effect of starved lubrication on elastohydrodynamic (EHL) line contacts. (February 2018) - Ebner, M.; Yilmaz, M.; Lohner, T.; Michaelis, K.; Höhn, B.-R.; Stahl, K.
Abstract: Highly-loaded EHL contacts in gears often operate under starved lubrication, albeit unintentionally. This is frequently correlated to mixed lubrication regimes resulting in reduced lifetime. Consequently, the aim of this study is to investigate the effect of starved lubrication on the operating behaviour of EHL contacts. Different amounts of initial oil volumes and surface structures were investigated by measuring the frictional behaviour at the FZG twin-disk test rig. Analytically calculated gap fill factors for initial oil volumes were assigned to the experiments. Results show that a very small amount of initial oil is sufficient for lubrication and different operating behaviours for peripherally ground, axially ground and polished surfaces. All experiments were accompanied by surface photos and roughness measurements. Highlights: Operational behaviour of EHL contacts under starved lubrication was investigated. Coefficient of friction was measured for different surface structures. Very small initial oil volumes were found to be sufficient for lubrication. Required minimal initial oil volume was found to differ with surface structures. Highest coefficient of friction was found for peripherally ground surfaces.